Batas Kedewasaan Anak untuk Cakap Hukum dalam Perspektif Peraturan di Indonesia - Mhd. Yadi Harahap (Journal of Gender and Social Inclusion in Muslim Societies, 2020)
The lack of uniformity in the age limit for adults or the age limit for children in various laws and regulations in Indonesia indeed often raises questions about which limits should be used. In addition, determining the minimum age a child can perform legal actions must obtain legal certainty and guarantee so that every act he does is legal before the law. The problem that arises is that until now the age limit of children is said to have grown up, there is no unification that applies in accordance with the provisions of the law, thus confusing people who can make ambiguity in determining when someone is declared an adult and capable of carrying out legal actions. To find a comprehensive answer and in-depth analysis, the method used in this study uses a normative juridical method with a statute approach, which is a law governing the minimum age limit for children referred to as adults in Indonesia. Related to the data used in this study is to combine primary data obtained and secondary data obtained from various references.